2019
DOI: 10.2478/ssa-2019-0003
|View full text |Cite
|
Sign up to set email alerts
|

The possibility of using sewage sludge for energy crop cultivation exemplified by reed canary grass and giant miscanthus

Abstract: Energy crops, on account of high biomass yields, have high nutrient requirements in relation to macroelements. Municipal sewage sludge can be a potential source of micronutrients for plants with high nutrient requirements. The use of macronutrients from sewage sludge by energy crops is an alternative form of nutrient recycling from organic waste. The aim of the research was to assess the content, uptake and use of N, P, K, Ca, Mg and Na from municipal sewage sludge by reed canary grass (Phalaris arundinacea L.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 34 publications
0
26
0
Order By: Relevance
“…Kubátová et al [18] observed the elevated yield of willows supported by SS fertilization from the second harvest, while the plant growth was limited in the first years. Several papers were published by the research group around Kołodziej and Antonkiewicz, which confirmed the positive effect of fertilization with SS on the biomass yield of energy plants from the Poaceae-Sorghum bicolor [19], Miscanthus × giganteus [20,21] and Phalaris arundinacea [21] families.…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…Kubátová et al [18] observed the elevated yield of willows supported by SS fertilization from the second harvest, while the plant growth was limited in the first years. Several papers were published by the research group around Kołodziej and Antonkiewicz, which confirmed the positive effect of fertilization with SS on the biomass yield of energy plants from the Poaceae-Sorghum bicolor [19], Miscanthus × giganteus [20,21] and Phalaris arundinacea [21] families.…”
Section: Introductionmentioning
confidence: 71%
“…This is in agreement with the previously published findings. A positive effect of SS as a soil amendment on the plant characteristics and biomass yield of other energy plants from the Poaceae family was described by the research group around Kołodziej and Antonkiewicz [19][20][21]. They observed a significant impact of the application of SS (10-60 t ha −1 ) on plant height, the number of leaves and the stems' diameter and dry weight of three cultivars of sweet sorghum [19].…”
Section: Evaluation Of Growth Parameters and Biomass Yield At The Endmentioning
confidence: 91%
See 1 more Smart Citation
“…Generally, there are two main approaches to be considered. The first approach is about influence to the soil by adding different amendments such as fertilizers [ 14 ], sludge [ 11 , 15 ], and biosolids [ 9 ], or incorporating to the system citric acid, EDTA [ 16 ], and fungi [ 17 ]. The second approach is focused on direct impact to rhizomes, which can be achieved by co-composting treatment, treatment by plant growth regulators [ 18 ], and incorporation of the microbial organisms [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Varieties of in situ and ex situ approaches are used for remediation of such areas, including surface capping, encapsulation, landfilling, soil flushing or washing, stabilization, solidification and phytoremediation and bioremediation (Liu et al 2018 ; Burges et al 2018 ). While the main techniques are rather costly and environmentally disturbing, the application of phytoremediation sounds promising, in particular with plants produced a high amount of biomass (Yadav et al 2018 ; Antonkiewicz et al 2019 ), and was recommended for post-industrial sites (Cunningham and Ow 1996 ; Chaney et al 2014 ). Guarino and Sciarrilli ( 2017 ) reported successful application of phytoremediation using two plants with high annual biomass yield: Helianthus annuus L. and Brassica juncea L. when a considerable amount of toxic elements (Cd, Hg, Zn) were taken from soils of the industrial area of Porto Marghera.…”
Section: Introductionmentioning
confidence: 99%